A comparison of three dispersion media on the physicochemical and toxicological behavior of TiO2 and NiO nanoparticles. (5th July 2015) - Gutierrez, Erika R.; Kamens, Richard M.; Tolocka, Michael; Sexton, Kenneth; Jaspers, Ilona
Highlights: Agglomeration of nanomaterials in media complicates dosing in in vitro studies. Dispersion media and surfactants differentially affect dose and toxicity endpoints. Toxicity endpoints are affected by exposure conditions including media height. Re-suspension methods yield inconsistent results which vary with concentration. Abstract: Nanomaterials represent a burgeoning field of technological innovation. With the onset of environmental release and commercial product exposure associated with nanomaterial manufacture and proliferation, the concomitant effects on human health remain unknown and demand further investigation. Agglomeration of nanomaterials in biologically relevant media used in in vitro methods further complicates dosing in toxicological study. Objective: to compare the effects of in vitro dispersion techniques on the physicochemical and toxicological dosimetry of TiO2 (<50 nm) and NiO (<20 nm) nanoparticles and some resulting toxicological endpoints to test for potential effects. Methods: three media were prepared for A549 and 16hbe14o cells with varying concentrations of TiO2 and NiO nanoparticles. Physicochemical effects were analyzed with dynamic light scattering, ICP-MS, SEM, and TEM. Toxicological effects were determined after stimulation of cells with nanoparticles for 4 and 24 h followed by analysis of inflammatory and oxidative stress markers with ELISA and RT-PCR. Our data show that dispersion media differentially affect physicochemical properties and toxicological endpoints. Therefore, we conclude that in vitro nanotoxicology models that use re-suspension methods of exposure yield inconsistent and misleading biological results due to physicochemical variation of particle characteristics and transport processes.